ANALYZING ECONOMIC FACTORS IN RESOURCE DISTRIBUTION FOR URBAN GROWTH - Andrews, Robert (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
In the ever-evolving landscape of urban development, the role of resources remains pivotal. This research delves into the dynamic relationship between emerging resources and the tertiary industry, offering a fresh perspective from the vantage point of urban planning. As society's demands for resources continue to expand and diversify, it becomes imperative to reevaluate the supply and allocation of these resources to sustain urban growth. Unlike traditional sectors, the tertiary industry presents a unique set of challenges and opportunities, intertwined with urban development. This study explores the intricate connections between industrial energy efficiency, value, output, and urban scale, transcending the traditional boundaries of economic analysis. By addressing the resource needs of the tertiary industry and aligning them with urban planning strategies, we aim to shed light on new pathways to overcome the urban development bottlenecks. This interdisciplinary approach offers a comprehensive view of how urban areas can harness emerging resources to foster sustainable growth.